2010
DOI: 10.1111/j.1464-410x.2010.09568.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and timing for intervention of partial adrenalectomy in patients with a solitary adrenal remnant and history of bilateral phaeochromocytomas

Abstract: Summary Objective To evaluate the outcomes and timing of intervention for adrenal sparing surgery in patients left with a solitary adrenal remnant after bilateral adrenal surgeries. Subjects/Patients and Methods Patients were included in the study if they had undergone bilateral adrenal surgery as a treatment for pheochromocytoma and were left with a solitary adrenal remnant. Perioperative, functional, and oncologic outcomes were evaluated on 21 patients that met the inclusion criteria. Results There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Finally, of four patients with a solitary adrenal gland, three patients did not require long-term treatment with steroid replacement after RALPA, indicating that the residual adrenal gland after RALPA was able to provide physiologic levels of endogenous steroids. These results are consistent with the findings of Sanford et al, evaluating outcomes of patients requiring adrenal surgery on a solitary adrenal [22]. Given the risks associated with bilateral adrenalectomy and uncertain dosing with exogenous steroids, it appears that adrenal-sparing surgery offers these patients a significant benefit.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, of four patients with a solitary adrenal gland, three patients did not require long-term treatment with steroid replacement after RALPA, indicating that the residual adrenal gland after RALPA was able to provide physiologic levels of endogenous steroids. These results are consistent with the findings of Sanford et al, evaluating outcomes of patients requiring adrenal surgery on a solitary adrenal [22]. Given the risks associated with bilateral adrenalectomy and uncertain dosing with exogenous steroids, it appears that adrenal-sparing surgery offers these patients a significant benefit.…”
Section: Discussionsupporting
confidence: 89%
“…3,4 A recent review of 417 patients undergoing PA found that the procedure was associated with minimal morbidity, a 3% recurrence rate, and the freedom from steroid replacement in 90% of patients. 5 It has been demonstrated that even the majority of patients with a solitary adrenal gland maintain independence from steroid use following PA. 6 To our knowledge, there is no literature on PA performed for synchronous multiple ipsilateral pheochromocytomas in a single setting. In this study, we report the perioperative, functional, and short-term oncologic outcomes of PA for multiple pheochromocytomas.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, because of a higher likelihood for bilaterality and genetic causes, the optimal management of adrenal pheochromocytoma in all-comers should consider adrenal preservation when technically feasible [54]. For patients with bilateral adrenal pheochromocytomas, a staged approach is recommended; moreover, intervention should take place before the tumors reach 4cm to allow for the best functional outcomes [55]. Partial adrenalectomy can be performed using pure laparoscopy or with robotic assistance [53, 56], and results in reasonable outcomes even in those patients with a solitary adrenal gland [57].…”
Section: Treatmentmentioning
confidence: 99%